Marketing digital como estratégia competitiva: o uso do portal digital do Banco do Brasil S.A. - (:unkn) unknown (Universidade Federal de Goiás, 2016)
The content covered in this dissertation, entitled "Digital marketing as a competitive strategy: Digital Portal using the Bank of Brazil SA" it is a descriptive and exploratory study. So describes the evolution of information technology in the banking sector and investigates the Digital Portal, available on the platform of this financial institution, contributes to a better relationship between customers three portfolios "Corporate" and that institution, as well as the advantages conferred on the use of it.
Digital marketing as competitive strategy: digital portal use the Bank of Brazil S.A.
Keywords: Consumidor; Estratégia competitiva; Marketing digital; Serviços bancários; Portal digital; Consumer; Competitive satrategy; Digital marketing; Bank services; Digital portal; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO